POSIÇÕES VERTICALIZADAS NO PARTO E A PREVENÇÃO DE LACERAÇÕES PERINEAIS: METANÁLISE - Rocha, Bruna Dedavid da (2017)
The model of obstetric and neonatal care at the national level, is experiencing important changes regarding the qualification and humanization of care. The importance of the insertion of obstetrical nurses in this scenario and the carrying out of research based on scientific evidence are highlighted. The objective was to perform a systematic review with meta-analysis to investigate whether the adoption of vertical positions by the woman, in childbirth, compared to the lithotomic position, prevents perineal lacerations. The first manuscript was an integrative review of literature, by searching the bases PubMed and Lilacs, on methods for prevention of perineal lacerations. The final sample consisted of 16 articles and emerged three thematic categories: factors related to the practice of episiotomy and the occurrence of perineal lacerations and indications for the performance, approach of the professional that provides assistance to normal delivery and strategies for prevention of perineal lacerations.The second manuscript concerns a systematic review. For this study, the Lilacs, Pubmed, Cinahl, Cochrane Library, Web of Science, Science Direct, Scopus, Google Schoolar and Open Gray databases were delineated as the main descriptors in english and portuguese: posture, second stage labor, posição and segunda fase de trabalho de parto. Moreover, only primary studies were carried out, which included parturients in active labor, who adopted vertical positions or lithotomic position at the time of delivery, and the prevention or not of perineal lacerations when adopting these positions. No temporal or language cut of studies was delimited. The relevance tests I and II were performed by two independent reviewers. The quality of the evidence was evaluated, according to the GRADE System, and meta-analysis of the results. Scientific evidence has emerged that it is not possible to say with certainty that vertical positions prevent perineal lacerations, compared to the lithotomic position. The product resulting from the research process is a systematic review with meta-analysis, which, based on evidence-based practice, is the best evidence available for clinical decision-making.